Life After Being a Pathology Department Chair III: Reflections on the “Afterlife” - Bailey, David N. (Acad Pathol, 2019)
The Association of Pathology Chairs Senior Fellows Group provided reflections on activities that have kept them engaged and inspired after stepping down as chair. They offered advice to current chairs who were considering leaving their positions and also to individuals contemplating becoming pathology chairs. A majority (35/41) responded: 60% maintained teaching/mentoring activities; 43% engaged in hobbies; 40% took other administrative positions including deans, medical center chief executive officers, and residency program directors; 31% continued research; 28% wrote books; 20% performed community service; 14% led professional organizations; 14% developed specialized programs; 11% engaged in clinical service; and 11% performed entrepreneurial activities. Most individuals had several of these activities. One-third indicated that those considering becoming chair should be able to place faculty and department needs before their own. One-fourth emphasized the need to know why one wants to become chair, the need to develop clear goals, and the need to know what one wants to accomplish as chair before applying for and accepting the position. More than half (57%) indicated that before stepping down as chair, one should have a clear plan and/or professional goals that can be served by stepping down. Some even suggested that this be in place before applying for the chair. Almost two-thirds (63%) indicated they had no regrets stepping down as chair. These findings may be valuable to those contemplating stepping down from or stepping into any department chair position or other academic leadership role.